Virtual Assisten Dengan Metode Rule Base Untuk UMKM Latitaka Borneo Berbasis Telegram - Devi Ayu Permatasari; Viny Christanti Mawardi; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
Latitaka Borneo MSMEs play a role in preserving local culture through typical Kalimantan herbal products. However, limitations in providing responsive customer service are a challenge amidst market competition. To overcome this problem, this research develops a virtual assistant based on a rule-based method that is integrated with the Telegram platform. This system is able to answer general questions, provide product information, and assist customers in the ordering process automatically. System testing involves evaluation using confusion matrices and cosine similarity to assess response accuracy and semantic relevance. The evaluation results show that the virtual assistant is able to increase operational efficiency and consistency of Latitaka Borneo services, so that it can better meet customer needs. It is hoped that this research can be a solution to increase the competitiveness of MSMEs through customer service automation.